The Latest Lyrics in the Aspect of Cross-Cultural Studies: The Problem of the Subject and the Phenomenon of Liminality (Review of the collective work: Neuere Lyrik. Interkulturelle und interdisziplinäre Studien: Subjekt und Liminalität in der Gegenwartsli (Филологический класс, 2021)
The article reviews the international collection of scholarly papers (in German and English) devoted to the study of the main trends in German and Russian poetry of recent decades “The latest lyrics. Cross-cultural and Interdisciplinary Studies: The Subject and Liminality in Modern Literature. Volume 2: Border Time – Genre Transit – Border”. Berlin, 2020. 497 p. The collection contains the articles by famous Germanists and Philologists-Slavists from Germany, Russia, the USA, Japan, etc. The reviewer focuses on the methodological specificity of the collective work, which is associated with the increased attention of the modern researcher to borderline (liminal) phenomena in the current Russian and German lyrics. Various creative and artistic practices of modern authors are considered “under the umbrella” of one problem – the problem of borders, thresholds and transitions. Liminal phenomena and new forms of subjectivity are studied based on poetic texts. This has determined the whole concept of compositional construction of the collection of articles. The reviewer maintains that the methodology proves effective when studying the peculiarities of Russian and German lyrical texts that have developed under the influence of radial shifts in the socio-cultural situation of the late twentieth century and the new turn of the century. The conclusion is made that this study in the aspect of intercultural relations recreates the holistic problematic picture of modern Russian and German lyrics.